Characteristics of Fall-Related Fractures in Older Adults with Cerebrovascular Disease: A Cross-Sectional Study - Fu M (Dove Medical Press, 2021)
Mingming Fu,1,* Junfei Guo,2,* Yuqi Zhao,1 Yaqian Zhang,1 Yingze Zhang,2– 4 Zhiqian Wang,1 Zhiyong Hou2,3 1Department of Geriatric Orthopedics, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Orthopaedic Surgery, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People’s Republic of China; 3NHC Key Laboratory of Intelligent Orthopeadic Equipment (The Third Hospital of Hebei Medical University), Shijiazhuang, Hebei, 050051, People’s Republic of China; 4Chinese Academy of Engineering, Beijing, 100088, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiqian WangDepartment of Geriatric Orthopedics, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaEmail w18533112890@163.comZhiyong HouDepartment of Orthopaedic Surgery, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaEmail drzyhou@gmail.comPurpose: Limited information exists on fall-related fractures in older adults with cerebrovascular disease. This study aimed to determine the characteristics of older adults with cerebrovascular disease who sustained fall-related fractures and identify the associated risk factors for perioperative complications.Patients and Methods: This was a cross-sectional study, which included patients with cerebrovascular disease who sustained fractures between Jan. 2017 and Dec. 2019. The collected data included demographics (age and gender), time and place of fracture occurrence, mechanism of injury, fracture location, type of cerebrovascular disease, complications, and comorbidities.Results: A total of 768 patients with 815 fractures were included; there were 253 males and 515 females, with an average age of 78.3 years. For either males or females, 80– 84 years was the most commonly involved age group. Most (61.0%) patients had their fractures occurring at home and most fractures (70.7%) occurred during the daytime. Most were hip fractures and limb weakness; instability-related falls were the most common cause of fracture, making a proportion of 34.5%. Patients who suffered falls were mainly combining ischemic cerebrovascular disease. Most (85.9%) patients presented with at least one comorbid disease and the perioperative complication rate was 76.9% in total cases. Age≥ 80 (OR: 1.772, 95% CI: 1.236– 2.540) and the number of comorbidities≥ 3 (OR: 1.606, 95% CI: 1.035– 2.494) were found independently associated with complications, while the type of cerebrovascular disease, fracture location, and comorbidities of prior fragility fracture and respiratory disease were not significantly correlated with complications.Conclusion: Our findings highlighted that more focus on improved physical function explored in intervention setting and the importance of primary home prevention measures seems justified in China and maybe other countries as well. It is the first study that presented the epidemiological characteristics of older adults with cerebrovascular disease who later experienced a fracture.Keywords: cross-sectional study, epidemiology, fall-related fracture, cerebrovascular disease, older adults